Histopathology of Intestine and Liver of Oreochromis niloticus Fed with Herbs Fermented and Infected with Aeromonas hydrophila - Dwi Indah Fransiska; Morina Riauwaty; Henni Syawal (Jurnal Akuakultur SEBATIN, 2024)
Natural ingredients used in the manufacture of fermented herbs medicine, such as turmeric, ginger, and kencur. These plants are antibacterial and antimicrobial and increase the growth of fish. This research was conducted from November 2021 to March 2022 at the Faculty of Fisheries and Marine, Riau University. The purpose of this study was to analyze the histopathology of the intestine and liver of Oreochromis niloticus fed with herbs fermented pellet and infected with Aeromonas hydrophila. The method used is an experiment with a completely randomized design (CRD) one factor, five levels of treatment, and three replications so that 15 experimental units were obtained. The treatments used were Kn (feeding without fermented herbs and without infection with A. hydrophila bacteria), Kp (feeding without fermented herbs and infected with A. hydrophila bacteria) and feeding with the addition of fermented herbs and infected with bacteria A. hydrophila at a dose of 150 mL/kg (P1), 175 mL/kg (P2), and 200 mL/kg (P3). The results showed that the damage that occurs in the intestine was edema, haemorrhage and necrosis. Liver damage in the form of hypertrophy, bleeding, vacuole degeneration and necrosis. The best dose was found which is 200 mL/kg of feed (P3). The survival rate was 85,00%. It can be concluded that the addition of herbs fermented to feed can improve the structure of O.niloticus